Reducing costs in atopic dermatitis. Issue 11 (9th October 2022) - Myers, Elisha M.; Perche, Patrick O.; Jorizzo, Joseph L.; Feldman, Steven R.
Abstract: Atopic dermatitis (AD) is a common relapsing inflammatory skin condition associated with a high economic burden due to its chronicity and multitude of direct and indirect treatment costs. AD disproportionately impacts children and minority populations, and treatment choices are cost‐prohibitive for many patients. Our objective was to describe the treatment and management of AD from a cost‐conscious perspective. A review of the literature was conducted with PubMed using the following keywords: AD, cost, medications, treatment, management, efficacy, adherence, education, and prophylactic. The use of moisturizers prophylactically in high‐risk infants who have yet to develop AD may reduce incidence of disease and associated costs. Increasing patient medication adherence and moisturizing between flares also reduces costs in AD. The use of corticosteroids as the first‐line treatment is efficacious and cost‐effective for mild cases of AD, however, in severe cases of AD corticosteroids alone are not sufficient. Systemic biologics are necessary in some patients with severe cases of AD; however, they are associated with high costs. Phototherapy, through portable home units, tanning beds, and natural sunlight are cost‐effective alternatives. Effective management of AD improves with education programs for both the patient and their family, reducing long‐term costs in the management of this disease. Reducing AD treatment costs requires consideration of prophylactic therapies, patient education, and should differ based on the severity of disease. A multifaceted approach to AD treatment reduces costs and health‐care barriers.